PARAMETRIC STUDY ON THE GEOMETRIC PARAMETERS OF CORRUGATED BLAST WALL - Hanmuhammet , Gayypov (Universiti Teknologi PETRONAS, 2017)
After some tragic incidents happened on offshore platforms due to some unexpected internal loads, such as hydrocarbon explosion or falling of a heavy material from top to a structure, the consequences had a huge impact on structure, economy, environment as well as human safety. As a solution, two methods have been suggested to overcome this problem, which are active and passive explosion proofs. Active explosion proof is the way of preventing the explosion before it happens, however, this way is considered expensive, also at the same time it is not fully reliable since it is based on theories of technical failure and human error is not considered. While the passive explosion proof is to reduce the consequences of an explosion after it happened, which is inexpensive compared to other options (Sohn et al. 2013). So far, as the best type of passive safety system, blast walls are being used broadly. Blast walls are designed to cover the vulnerable structures on top side of the offshore platform to absorb the pressure after the explosion occurred. The challenge that is being faced in this case is to obtain the optimum geometric parameters and material type in terms of cost and performance, that can withstand against various loading conditions. However, to do so, numerous simulations have to be conducted to obtain the results, which decision will be based on. By varying all parameters, numerous cases will be created which is too time consuming to analyze and study. Aim of this paper is to determine most and least significant parameters. Two materials are being used, with the various material properties, those are High Manganese and 9% Nickel.